Development and prospect of supercritical CO2 pipeline transmission technology in China - Duihong ZHANG; Yuxing LI (You-qi chuyun)
Objective Amidst the ongoing pursuit of "dual carbon" goals, Carbon Capture, Utilization, and Storage (CCUS) has rapidly progressed as a foundational technology facilitating significant carbon emission reductions in China. Serving as a crucial link between upstream and downstream activities in the CCUS industry chain, the construction of CO2 pipelines is capitalizing on its golden development opportunities. To propel the construction and growth of CO2 pipelines in China, a relative latecomer in this realm, it is imperative to systematically address key challenges and core technologies associated with CO2 pipeline transmission while establishing a comprehensive technical standard system. Methods Literature research was undertaken to review and evaluate the current development status of CO2 pipeline transmission technologies. The significant advancements in CO2 pipeline transmission technologies were summarized through an in-depth analysis of various facets such as CO2 phase behaviors, the pipeline transmission process, pipeline safety, software simulations, and standards and specifications. Recommendations and future outlooks for planning CO2 pipelines and developing pipeline transmission technologies were delineated, considering the distinctive characteristics of carbon sources and sinks in China. Results In contrast to European nations and the United States, China faces a shortage in establishing long-distance supercritical CO2 pipelines. Currently, the only operational project is a dense phase CO2 pipeline linking the facilities of Sinopec Qilu Petrochemical Company (Qilu Petrochemical) with Shengli Oilfield. Additionally, the CO2 pipeline projects of PetroChina Daqing Petrochemical Company (Daqing Petrochemical) and Sinopec Jilin Oil Products Company (Jilin Petrochemical) remain in the preliminary design phase. As a result, it is foreseeable that the pace of CO2 pipeline construction in China will increase in the future. Conclusion China has developed a certain level of technical expertise for supercritical CO2 pipeline transmission. However, additional endeavors are required to address challenges in pilot testing and enhance theoretical models. Simultaneously, there is a need to advance engineering applications to demonstrate related technologies and enhance the standard system of CO2 pipeline transmission technologies. These steps are crucial to offer extensive and strong support for planning and building regional ten-million-ton CO2 pipeline transmission networks and interregional CO2 trunk pipelines in the future.